2014
DOI: 10.1007/s40843-014-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of semiconductor photocatalyst for photocatalytic reduction of CO2 to solar fuel

Abstract: The shortage of fossil fuels and the disastrous pollution of the environment have led to an increasing interest in artificial photosynthesis. The photocatalytic conversion of CO 2 into solar fuel is believed to be one of the best methods to overcome both the energy crisis and environmental problems. It is of significant importance to efficiently manage the surface reactions and the photo-generated charge carriers to maximize the activity and selectivity of semiconductor photocatalysts for photoconversion of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
298
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(310 citation statements)
references
References 361 publications
(509 reference statements)
5
298
0
Order By: Relevance
“…As compared in Fig. 6c, the NMGCN powder shows a lower PL emission intensity than the GCNN case, suggesting the lower charge recombination rate in the NMGCNs [14,46,47]. A blue shift of the maximum emission peak was also observed in the PL spectrum of the NMGCN powder, which was in agreement with the above DRS results.…”
Section: Resultssupporting
confidence: 88%
“…As compared in Fig. 6c, the NMGCN powder shows a lower PL emission intensity than the GCNN case, suggesting the lower charge recombination rate in the NMGCNs [14,46,47]. A blue shift of the maximum emission peak was also observed in the PL spectrum of the NMGCN powder, which was in agreement with the above DRS results.…”
Section: Resultssupporting
confidence: 88%
“…Ehsan p-n heterojunctions. [25][26][27][28][29] The narrow bandgap of these guest semiconductors favors visible-light absorption and accelerates the separation of electrons/hole (e À /h + )p airs owing to the potential differencea cross the p-n junction. It has been reported that solar cells based on II-VI semiconductors (Zn, Cd, Hg and S, Se, Te)p rove to be prominent candidates for low-cost photovoltaic conversion of solar energy due to their high absorption coefficient and low material consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen generation from solar energy can be achieved by splitting water using semiconductor materials based photocatalytic and photoelectrochemical (PEC) cells [1][2][3]. Particularly, one-dimensional (1D) nanostructures are prevalent for water splitting applications and have been widely investigated as photoelectrodes, due to their shorter carrier transport path and larger surface-to-volume ratio related with more reaction sites [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%